Flexural behaviour of fibre-reinforced polymer–aluminium sandwich curtain walls. (October 2018) - Liu, Yang; Kuang, JS; Chan, BYB
A new type of fibre-reinforced polymer–aluminium sandwich curtain wall panel, which consists of layers of aluminium plate, fibre-reinforced polymer plate, foam core and gypsum board, was proposed to achieve high strength and stiffness, efficient energy saving and good fire resistance for the modern curtain wall systems in buildings. An experimental study was conducted to investigate the flexural behaviour of the fibre-reinforced polymer–aluminium composite curtain wall panels. Three groups of large-scale specimens with different thickness of foam core with and without a phase change material layer were tested under uniformly distributed loads. The test results showed that due to the asymmetric arrangement of sandwich layers, the loading directions had a significant effect on the flexural behaviour of the panels with and without a phase change material layer. It was also shown that with the increase of the foam core thickness, the flexural behaviour of panels was significantly improved. In addition, the phase change material layer had little effect on the flexural behaviour of the sandwich panels under and beyond the serviceability conditions, but significantly reduced the serviceability strength.